A novel thiourea‐based fluorescent turn‐on sensor for rapidly detecting hypochlorite through a desulfurization reaction - Choi, Boeun; Kim, Soyeon; Kim, Cheal (Bulletin of the Korean Chemical Society, 2024)
Excess hypochlorite (ClO−) is harmful to living organisms and can cause various oxidative diseases in the human body. Owing to the toxicity of ClO−, the development of efficient fluorescence sensors to track ClO− is necessary. In this work, we report a novel thiourea‐based fluorescent turn‐on sensor 1‐(9‐ethyl‐9H‐carbazol‐3‐yl)‐3‐(naphthalen‐1‐yl)thiourea (ECNT) for recognizing ClO−. ECNT can detect ClO− with high selectivity, relatively low interference with other analytes, and a significantly fast response time (<1 s) through a desulfurization reaction. The detection limit of ECNT for ClO− is calculated as 5.59 μM. Of note, ECNT is a chemosensor that reacts the fastest with ClO− among the reported thiourea‐based fluorescence turn‐on sensors for detecting ClO−. The response mechanism of ECNT to ClO− is demonstrated through 1H NMR titration, ESI mass, and density functional theory calculations. A novel thiourea‐based fluorescent turn‐on sensor 1‐(9‐ethyl‐9H‐carbazol‐3‐yl)‐3‐(naphthalen‐1‐yl)thiourea was developed for recognizing ClO− with a significantly fast response time (<1 s) through a desulfurization reaction. The response mechanism of 1‐(9‐ethyl‐9H‐carbazol‐3‐yl)‐3‐(naphthalen‐1‐yl)thiourea to ClO− was demonstrated through 1H NMR titration, ESI mass, and density functional theory calculations.